Persanura hyrcanica, a new genus and species of Neanurinae (Collembola: Neanuridae) from Iran, with a key to genera of the tribe Neanurini - Mayvan, Mahmood Mehrafroz; Shayanmehr, Masoumeh; Smolis, Adrian; Skarżyński, Dariusz (Zootaxa, 2015)
Persanura hyrcanica, a new genus and species of Neanurini from Iran is described and illustrated. It has a unique suite of morphological characters: labrum with only 4 chaetae, fusion of tubercles So and L on head, tubercle Di on th. II–III with 2 chaetae and separation of tubercles Di on abd. V. The erected genus is closely related to Neanura MacGillivray, 1893, Kalanura Smolis, 2007 and Xylanura Smolis, 2011. An updated key to genera of the tribe Neanurini is given.